2003
DOI: 10.1300/j027v22n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Rationing Home Care Resources: How Discharged Seniors Cope

Abstract: Rationing home care services has become a common strategy used by state/provincial governments to control escalating health care costs, particularly at a time when very little new funding has been re-directed to the home care sector. Across British Columbia, Regional Health Authorities had implemented service reforms that call for the discharge of higher functioning clients from home support service. This paper describes the coping strategies of 137 senior clients who were discharged from home support services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Provincial budget cuts to home care services and the resulting changes to the eligibility criteria along with eliminating a certain level of services have led to discharge of senior clients from the service. A qualitative study investigated coping strategies among those clients and revealed that 34 per cent were suffering in silence with feelings of abandonment, loneliness, and betrayal (Livadiotakis, Gutman, & Hollander, 2003). Another 29 per cent were receiving assistance from informal sources or were paying for private care, while 28 per cent adapted to doing the activities previously supported through home care by themselves (Livadiotakis, Gutman, & Hollander, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Provincial budget cuts to home care services and the resulting changes to the eligibility criteria along with eliminating a certain level of services have led to discharge of senior clients from the service. A qualitative study investigated coping strategies among those clients and revealed that 34 per cent were suffering in silence with feelings of abandonment, loneliness, and betrayal (Livadiotakis, Gutman, & Hollander, 2003). Another 29 per cent were receiving assistance from informal sources or were paying for private care, while 28 per cent adapted to doing the activities previously supported through home care by themselves (Livadiotakis, Gutman, & Hollander, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…There was a tendency among patients to withdraw from social activities due to the social stigmatization and technical barriers of these interventions. Livadiotakis et al, 2003 Qualitative study; personal interviews -Simon Fraser Health Region, British Columbia 137 senior clients discharged from home support services 19 to 21 months after discharge clients' coping themes; 34.3% of clients were "home alone and suffering in silence" including feeling abandoned, lonely, and betrayed; 29.2% were receiving assistance from informal sources or reported paying out-of-pocket for private care; and 28.4% were able to do their work better themselves as they were unhappy with formal service, and 8% were having "mixed feelings". Lo et al, 2015 Retrospective cohort study -Ontario 119,795 older clients receiving long-stay home care services…”
Section: Hebert Et Al 2010mentioning
confidence: 99%
“…Participants in this study were institutionalized over a ten-year period from 1991 to 2001, during which changes in health-care policy in British Columbia may have impacted the provision of health-care services, and may make these results cohort specific. For example, there were reductions in available hospital and institutional beds, ( 44 ) discharge of many seniors from institutions and home care programs, ( 45 ) and the introduction of a streamlined regional health-care model. ( 46 ) However, similar results from research conducted in the adjacent province of Alberta, which underwent its own policy changes, ( 47 ) support the generalizability of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-based care is closely aligned with treating the acute phases of disease with interventions focused on improving or maintaining clients’ status (Stanhope & Lancaster, 2012). These systems are increasingly taxed by shorter hospital stays, deepening budget cuts, and readmissions to acute care (CIHI, 2012; Livadiotakis, Gutman, & Hollander, 2008). Lalonde (1974) had cautioned against the economic risks of remaining entrenched in a medical mind-set that focuses on the diagnosis: “The consequence of the traditional view is that most direct expenditures on health are physician-centered, including medical care, hospital care, laboratory tests, and prescription drugs” (p. 12).…”
Section: Introductionmentioning
confidence: 99%